Generation of a functional liver tissue mimic using adipose stromal vascular fraction cell-derived vasculatures - Nunes, S. S. (Nature Publishing Group, 2013)
One of the major challenges in cell implantation therapies is to promote integration of the microcirculation between the implanted cells and the host. We used adipose-derived stromal vascular fraction (SVF) cells to vascularize a human liver cell (HepG2) implant. We hypothesized that the SVF cells would form a functional microcirculation via vascular assembly and inosculation with the host vasculature. Initially, we assessed the extent and character of neovasculatures formed by freshly isolated and cultured SVF cells and found that freshly isolated cells have a higher vascularization potential. Generation of a 3D implant containing fresh SVF and HepG2 cells formed a tissue in which HepG2 cells were entwined with a network of microvessels. Implanted HepG2 cells sequestered labeled LDL delivered by systemic intravascular injection only in SVF-vascularized implants demonstrating that SVF cell-derived vasculatures can effectively integrate with host vessels and interface with parenchymal cells to form a functional tissue mimic.